Dobrovolná služba vlasti. Zájem o vstup do aktivní zálohy Armády ČR v době krize - Bubanec, Jan (Lidé města, 2024)
This article focuses on the motivations of candidates for service in the Active Reserve or for completing Voluntary Military Training. In the context of the ongoing war in Ukraine, people’s interest in service is sharply rising. Thus, the main research objective is to shed light on the motivations for serving in the military in the context of the proximity to potential threats, for which I used the qualitative research methods of semi-structured interview analysis, participant observation, social network analysis, and secondary data. In this article, I provide an overview of the existing research and introduce concepts through which the Active Reserve Institute can be perceived, especially the concepts of responzibilization and that of reserve soldiers being transmigrants. This article is the output of a completed bachelor thesis on the topic. It contains a cross-section of this work and its findings, which show the need for new motivation categories and how the presence of potential conflict affects the perception of defense in the eyes of society.